HUBUNGAN NEGARA DAN AGAMA ( STUDI KASUS PERAN AKTOR RELIGIUS DALAM KONSTELASI POLITIK TIMOR - LESTE ) - Duarte, Efatha Filomeno Borromeu; Erviantono, Tedy; Azhar, Muhammad Ali (Jurnal Nawala Politika, 2016)
ABSTRACT The role of the Catholic Church Timor - Leste brings an interesting dimension in which the occurrence of a marriage between the State and Religion. The influence of the Catholic Church has existed since 450 years in Timor - Lifau to be Timor - Leste. The Church is so varied in their efforts to draw closer to the public for increasingly legitimized in the heart of the community it creates religious actors who have a role in the political constellation Timor - Leste. Period - a difficult period experienced by Timor - Leste in 2006 there has been a mess as a democratic state where the Timor - Leste should be able to run a good election no wonder the Church does not remain silent but the Church falls directly to supervise elections in 2007. And what about the actors religious view politics itself using qualitative research - verification also direct observation using deliberative democracy theory analysis on the relationship of state and religion to see the influence of religious actors of the State and this study will prove the role of religious actors in the political constellation Timor - Leste. Keywords: Religious Actor, constellation, relationship between the State and Religion